Existence of a classical solution to complex material flow problems. (1st February 2016) - Che, Jiahang; Chen, Li; Göttlich, Simone; Wang, Jing
Abstract : An existence result of smooth solutions for a complex material flow problem is provided. The considered equations are of hyperbolic type including a nonlocal interaction term. The existence proof is based on a problem‐adapted linear iteration scheme exploiting the structure conditions of the nonlocal term. 35Q70, 35L65 Copyright © 2016 John Wiley & Sons, Ltd.